Kinetics of single session intra-individual difference in sprint acceleration: a case study - Nagahara, R. (ISBS Proceedings Archive (Michigan), 2018)
This case study aimed to investigate inter-repetition differences in joint kinetics for a single athlete during the acceleration phase of sprinting. One well-trained male sprinter performed three maximal effort 40-m sprints in an indoor experimental site. Using the fastest and slowest trials, spatiotemporal, ground reaction forces, and joint moment variables were calculated step to step for 16 steps. The fastest trial was accompanied by the greater mean net anteroposterior force. Moreover, there were greater hip extension and ankle plantar flexion moments, as well as a smaller knee extension moment, in the fastest trial. Accordingly, producing greater hip extension and ankle plantar flexion moments while suppressing the knee extension moment leads to better sprint acceleration through the greater propulsive force in the initial acceleration section.